Efficient delivery of genome-editing proteins using bioreducible lipid nanoparticles - Wang, Ming; Zuris, John A.; Meng, Fantao; Rees, Holly; Sun, Shuo; Deng, Pu; Han, Yong; Gao, Xue; Pouli, Dimitra; Wu, Qi; Georgakoudi, Irene; Liu, David R.; et al. (Proceedings of the National Academy of Sciences - PNAS, 2016)
A central challenge to the development of protein-based therapeutics is the inefficiency of delivery of protein cargo across the mammalian cell membrane, including escape from endosomes. Here we report that combining bioreducible lipid nanoparticles with negatively supercharged Cre recombinase or anionic Cas9:single-guide (sg)RNA complexes drives the electrostatic assembly of nanoparticles that mediate potent protein delivery and genome editing. These bioreducible lipids efficiently deliver protein cargo into cells, facilitate the escape of protein from endosomes in response to the reductive intracellular environment, and direct protein to its intracellular target sites. The delivery of supercharged Cre protein and Cas9:sgRNA complexed with bioreducible lipids into cultured human cells enables gene recombination and genome editing with efficiencies greater than 70%. In addition, we demonstrate that these lipids are effective for functional protein delivery into mouse brain for gene recombination in vivo. Therefore, the integration of this bioreducible lipid platform with protein engineering has the potential to advance the therapeutic relevance of protein-based genome editing.